Development of RAPD technique for plant DNA fingerprinting in Malaysia - Muhammad Yusran, Abdul Aziz (PPSP, Universiti Sains Malaysia, 2007)
Random amplified polymorphic DNA (RAPD) molecular markers have been widely used in analysis of plant genetic diversity, particularly at species and infraspecific levels. In this research, RAPD was used to study the genetic markers of plants. Three plants selected for this study are Mitragyna speciosa, Nicotiana spp., L and Centella asiatica. RAPD analysis was carried using seven arbitrary primers of 10 base pair each. Polymerase chain reaction was optimized by varying the DNA concentration, primer concentration and annealing temperature. Each species is represented by the number of scorable band produced. Further optimization is required in order to obtain better quality and quantity of PCR products.